2019
DOI: 10.1038/s41467-019-10711-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of PS 18:0/18:1 in membrane function

Abstract: Various studies have demonstrated that the two leaflets of cellular membranes interact, potentially through so-called interdigitation between the fatty acyl groups. While the molecular mechanism underlying interleaflet coupling remains to be fully understood, recent results suggest interactions between the very-long-chain sphingolipids in the outer leaflet, and phosphatidylserine PS18:0/18:1 in the inner leaflet, and an important role for cholesterol for these interactions. Here we review the evidence that cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 78 publications
(87 citation statements)
references
References 111 publications
3
83
1
Order By: Relevance
“…Interesting in this connection is the remarkably similar enrichment of CHOL, SM, and PS from CHO cells to detergent-resistant membranes (DRMs) as well as rafts isolated without detergent [21] as the enrichments observed for these lipid classes in exosomes excreted from PC-3 cells [20]. In a recent review, we discussed the role of PS18:0/18:1 in membrane function and showed that data published from several laboratories indicate that this lipid species has an important function in coupling the two leaflets due to interactions with sphingolipids and CHOL [10].…”
Section: Ps In Lipid Rafts and Caveolaementioning
confidence: 99%
See 4 more Smart Citations
“…Interesting in this connection is the remarkably similar enrichment of CHOL, SM, and PS from CHO cells to detergent-resistant membranes (DRMs) as well as rafts isolated without detergent [21] as the enrichments observed for these lipid classes in exosomes excreted from PC-3 cells [20]. In a recent review, we discussed the role of PS18:0/18:1 in membrane function and showed that data published from several laboratories indicate that this lipid species has an important function in coupling the two leaflets due to interactions with sphingolipids and CHOL [10].…”
Section: Ps In Lipid Rafts and Caveolaementioning
confidence: 99%
“…The different conclusions drawn from such studies strongly suggest that some of the methods used cannot be trusted, and we refer to an excellent review article where this controversial issue is summarized [15]. Based on the very high content of CHOL in some membranes, we find it difficult to understand how CHOL can be located mainly in one of the two leaflets, as we recently have discussed [10].…”
Section: Distribution Of Chol In the Pm And Lipid Raftsmentioning
confidence: 99%
See 3 more Smart Citations